Left internal mammary artery to pulmonary artery fistula causing coronary steal syndrome: A review of literature on therapy, intervention, and management. Issue 1 (3rd April 2019) - Olson, Peter C.; Spagnola, Jonathan; Nalluri, Nikhil; Tamburrino, Frank
Abstract: Coronary artery anomalies (CAA) are anatomical aberrations in the origin, structure, and course of the epicardial arteries. Literature has detailed common anomalies or fistulas formed because of coronary artery bypass grafting (CABG) manipulation of intrathoracic vessels. Despite the commonality of the CABG procedure, there are a few CAA and fistula findings which remain extremely rare. We present a case of left internal mammary artery to pulmonary artery fistula causing coronary steal syndrome that presented symptomatically as a malignant arrhythmia. Following a literature review of therapy, intervention, and management we recommend a team based approach when faced with this extremely rare case presentation. The goal of management should to reduce symptoms, and ischemia, by reducing or stopping flow through the fistula and out of the coronary blood supply.